(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
The importance of chemical and mechanical investigations of soil and water in laboratory as well as at site for establishing durable foundation work by way of identifying deleterious factors is inevitable for any durable concrete structure. These factors clearly identify the type of the mix design applicable to cope with the aggressive environments under which the piles subjected to be established. An inherent durability problem can be tackled by taking into account the identified deleterious constituents present in the environment in which the piles are to be placed. The paper focuses on the types of possible damages to occur and its remedial measures thereof.